Type-2 epithelial-mesenchymal transition in oral mucosal nonneoplastic diseases - Meng, Zhaosong; Yang, Tianle; Liu, Dayong (Frontiers in Immunology, 2022)
The oral mucosa is a membranous structure comprising epithelial and connective tissue that covers the oral cavity. The oral mucosa is the first immune barrier to protect the body against pathogens for systemic protection. It is frequently exposed to mechanical abrasion, chemical erosion, and pathogenic invasion, resulting in oral mucosal lesions, particularly inflammatory diseases. Epithelial-mesenchymal transition (EMT) is a crucial biological process in the pathogenesis of oral mucosal disorders, which are classified into three types (types 1, 2, and 3) based on their physiological consequences. Among these, type-2 EMT is crucial in wound repair, organ fibrosis, and tissue regeneration. It causes infectious and dis-infectious immunological diseases, such as oral lichen planus (OLP), oral leukoplakia, oral submucosal fibrosis, and other precancerous lesions. However, the mechanism and cognition between type-2 EMT and oral mucosal inflammatory disorders remain unknown. This review first provides a comprehensive evaluation of type-2 EMT in chronically inflammatory oral mucosal disorders. The aim is to lay a foundation for future research and suggest potential treatments.